Screening for inhibitors of the Mycobacterium tuberculosis DnaK-DnaJ-GrpE complex - John, Ruth Omoti (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Bioinformatics)
Restricted access. Expected release in 2026.
Keywords: Uncatalogued